Unlocking Potential: The Transformative Role of Gaming in Rural Higher Learning Institutions of South Africa - A Systematic Exploration - Mbukanma, Ifeanyi; Manganyi, Madira; Vellem, Bhekithemba; Gqoli, Neliswa (Research in Social Sciences and Technology, 2024)
The aim of this study resonated with the pursuit of achieving enhanced engagement in teaching and learning that informs critical thinking, and knowledge retention among students. Despite the growing trend of technological integration in teaching and learning, however, there exists a lack of empirical evidence and comprehensive studies that investigate the effectiveness of gaming in promoting educational objectives within rural institution of higher learning in South Africa. To investigate this gap, a systematic review method was employed, which provides a comprehensive and logical analysis of existing literature on the significance of gaming in teaching and learning within rural institutions of higher education. Inclusion and exclusion criteria were used in the study to enhance the rigor and transparency of the research process, by providing a solid foundation for synthesizing and interpreting existing literature relevant to the study. The systematic review findings revealed that the significance of gamification in teaching and learning in rural higher education lies in its ability to overcome accessibility challenges, provide personalized learning experiences, address motivation and retention issues, and enhance digital literacy. It was recommended that by incorporating gamified approaches, rural higher educational institutions can create a more inclusive, engaging, and effective learning environment for students within the rural institutions of higher learning in South Africa.